ERRATUM TO ÂSECOND-ORDER PLASTIC-ZONE ANALYSIS OF STEEL FRAMES, PART I: NUMERICAL FORMULATION AND EXAMPLES OF VALIDATIONÂ - ALVES, MARCILIO (2009)
ERRATUM TO ÂSECOND-ORDER PLASTIC-ZONE ANALYSIS OF STEEL FRAMES,PART I: NUMERICAL FORMULATION AND EXAMPLES OF VALIDATIONÂ